The Environmental and Economic Impact of the State of Emergency in Rivers State, Nigeria - Udoinyang, Nathan (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study investigates the environmental and economic impact of the state of emergency in Rivers State, Nigeria. The study used a mixed-methods approach, combining quantitative and qualitative data to compile it population. The population of the study was estimated as 5,198,716 by the Nigeria Population Commission (NPC) in 2006 and a sample size of 400 was achieved by using the Taro Yamane formula. Researchers circulated 400 questionnaires and collected 295 of them. Using a mean criterion of 3.0, the questionnaire was evaluated using a 5-point Likert scale, SPSS, and Cronbach's alpha correlation of 0.80 was employed in its data analysis. The findings of the study reviewed that the environmental and economic impacts of the state of emergency in Rivers State are water pollution, oil spillage, loss of ecosystem, increased poverty, unemployment, social unrest, decrease in revenue, displacement of people, etc. The study concluded and recommended that the government should take immediate action to address the environmental and economic impacts of the state of emergency by providing support to affected businesses and households, investing in infrastructure and security, and promoting economic diversification and development in the state.